2020
DOI: 10.1002/lno.11414
|View full text |Cite
|
Sign up to set email alerts
|

Harmful alga trades off growth and toxicity in response to cues from dead phytoplankton

Abstract: Organisms are under selection pressure to recognize predators and assess predation risk to avoid becoming prey. In some cases, the presence of injured competitors alerts individuals to the likelihood that predators are nearby. Previous studies have shown that the marine dinoflagellate Alexandrium minutum responds to chemical cues from copepods by dramatically upregulating sodium channel-blocking toxins that appear to function as defenses against copepod grazing. However, it is unknown whether A. minutum uses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…and did not find any correlation between growth rate and toxin production under light-replete conditions, and even a positive correlation under limiting light. Brown & Kubanek [11] recently demonstrated a negative relation between toxin content and growth rate in Alexandrium minutum exposed to lysed cells of various other species of dinoflagellates, thus suggesting a trade-off. However, the correlation may also result from allelochemical substances in the lysed cells reducing growth [12].…”
Section: Introductionmentioning
confidence: 99%
“…and did not find any correlation between growth rate and toxin production under light-replete conditions, and even a positive correlation under limiting light. Brown & Kubanek [11] recently demonstrated a negative relation between toxin content and growth rate in Alexandrium minutum exposed to lysed cells of various other species of dinoflagellates, thus suggesting a trade-off. However, the correlation may also result from allelochemical substances in the lysed cells reducing growth [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is also known that Alexandrium spp. can modulate its allelochemical potency against microalgae in response to changing physicochemical conditions (Martens et al ., 2016; Long et al ., 2019) but also its toxicity in response to cues from dead microalgal cells (Brown & Kubanek, 2020). It was also observed that genes associated with defensive responses such as the production of reactive oxygen species were overexpressed in a non-allelopathic strain of A. fundyense exposed to Amoebophrya sp.…”
Section: Discussionmentioning
confidence: 99%
“…After about 40 h, all cultures were harvested with processing of treatments and controls intermixed over about 2.5 h within 4 h of the start of the light cycle. An aliquot of each culture was harvested by centrifugation for targeted toxin analysis of GTXs 1–4, using methods similar to those described in Brown and Kubanek (2020), and an unpaired Welch's t ‐test was performed in GraphPad Prism 9.0 to compare toxin concentrations between treatments and controls. The remaining portion of each culture was harvested by vacuum filtration and extracted in a manner similar to Poulson‐Ellestad et al (2014).…”
Section: Methodsmentioning
confidence: 99%